Propuesta interdisciplinaria para la indagación en las ciencias naturales en estudiantes de séptimo grado: una investigación de diseño en el aula - Cárdenas Pérez, Robinson (Universidad Antonio Nariño, 2023)
This work evaluated the results of the implementation of an interdisciplinary didactic proposal in chemistry, biology, and physical education, with the aim of promoting the competence of inquiry in natural sciences. The study was conducted with 38 7th grade students and three teachers at a school in Soacha, Colombia. Design-Based Research (IBD) was used and information was collected through field diaries, semi-structured interviews, and the Saber 7 2021 test evaluation questionnaire.